Prognostic Relationship Between Coronary Artery Calcium Score, Perfusion Defects, and Myocardial Blood Flow Reserve in Patients With Suspected Coronary Artery Disease. (13th April 2022) - Patel, Krishna K.; Peri-Okonny, Poghni A.; Qarajeh, Raed; Patel, Femina S.; Sperry, Brett W.; McGhie, A. Iain; Thompson, Randall C.; Kennedy, Kevin F.; Chan, Paul S.; Spertus, John A.; Bateman, Timothy M.
Abstract : Background: Coronary artery calcium score (CACS) is an anatomic measure of calcified atherosclerosis. Myocardial perfusion defects and reduced myocardial blood flow reserve (MBFR) are physiological measures of ischemia and coronary circulatory health. We aimed to assess the relative prognostic importance of MBFR, perfusion defects, and CACS in patients with suspected coronary artery disease. Methods: A total of 5983 consecutive patients without known history of coronary artery disease or cardiomyopathy, who underwent a CACS and 82 Rb positron emission tomography myocardial perfusion imaging between 2010 and 2016, were followed for all-cause death (n=785) over median of 3 years. Prognostic value was assessed using multivariable Cox regression models, and incremental risk discrimination for imaging variables was evaluated by comparing model c-indices after adjusting for clinical risk factors (RF). Results: Mean age was 67.1 years, 60% were female, and 83% were symptomatic. CACS was 0 in 22%, abnormal perfusion in 19%, and MBFR <2 in 53.3%. When added to RF, the model with MBFR had the best fit (c=0.78, P <0.0001). Addition of CACS to model with RF and perfusion (c=0.77) offered modest improvement in discrimination over the model with RF and perfusion (c=0.76, P =0.02). Adding CACS to a model with RF, perfusion, and MBFR did not provide incremental prognostic value (c=0.785 for both, P =0.16). CACS and MBFR both had independent prognostic value in patients with normal and abnormal myocardial perfusion imaging. Even among patients with CACS of 0, MBFR <2 was present in 37.8%, being associated with higher risk of death (hazard ratio per 0.1↓, 1.10 [1.04–1.15]; P <0.001), but perfusion defects were not. Conclusions: Use of anatomic testing such as CACS of 0 to avoid myocardial perfusion imaging in symptomatic patients could lead to missing microvascular dysfunction in 4 out of 10 patients, a finding associated with a high mortality risk. Higher CACS was independently associated with the risk of death but did not provide incremental prognostic value over positron emission tomography with MBFR.